2022
DOI: 10.1007/s12032-022-01814-9
|View full text |Cite
|
Sign up to set email alerts
|

Valeric acid acts as a novel HDAC3 inhibitor against prostate cancer

Abstract: Prostate cancer is the second cause of cancer-related deaths in men worldwide, and new agents for curing the disease are still needed. In this study, we theoretically and experimentally demonstrated that valeric acid (VA) was a HDAC inhibitor, and anti-cancer efficacy of VA in prostate cancer cells was also observed using either 2D or 3D culture systems. VA was cytotoxic for prostate cancer cells but low toxic to normal cells. VA significantly inhibited E2F1/E2F3 expression but increased CASP3 activity. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The present meta-analysis revealed that an excessive dietary intake of total SFAs increases the risk of cancer, although this does not imply that SFAs are invariably detrimental. A few SFAs are reported to inhibit certain types of cancers [ 72 75 ]. In addition to high levels of SFA in the diet, the other dietary components may also promote cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present meta-analysis revealed that an excessive dietary intake of total SFAs increases the risk of cancer, although this does not imply that SFAs are invariably detrimental. A few SFAs are reported to inhibit certain types of cancers [ 72 75 ]. In addition to high levels of SFA in the diet, the other dietary components may also promote cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While a few studies have reported the role of butyric acid in combating colon cancer [ 90 92 ], the present study revealed no association between elevated butyric acid levels and the risk of cancer. According to certain previous research, propionic acid could inhibit breast and colorectal cancers [ 73 , 74 ] and valeric acid could inhibit prostate and breast cancers [ 72 , 75 ]. However, in the present meta-analysis, propionic and valeric acids were not evaluated for their association with cancer due to the unavailability of sufficient data in the literature, which if used, could have yielded inconclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, pentadecanoic acid exerted more potent HDAC6 inhibitory effects with binding energies 2,2-dimethylbutyric acid, 2-ethylbutyric acid, and valproic acid, and the un-branched fatty acids propionic acid, valeric acid and butyric acid, were previously identified as weak and equipotent HDAC inhibitors, respectively (22). In a recent study, valeric acid was identified as a HDAC3 inhibitor (23).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were maintained at 37 °C in a 5% CO 2 humidified incubator. The hanging-drop method was used to enable cellular spheroid formation which has been described in a previous method . Approximately 1,000 SW48 KRAS WT and SW48 KRAS G12A cells were in each drop (20 μL).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The hanging-drop method was used to enable cellular spheroid formation which has been described in a previous method. 15 Approximately 1,000 SW48 KRAS WT and SW48 KRAS G12A cells were in each drop (20 μL). The imaging of 3D CRC spheroids was taken on day 7 using a ZEISS Zen 3.3 (blue edition) microscope software.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%